VIOLATIONS AND LAW ENFORCEMENT AGAINST MARK VIEWED FROM LAW NO. 20 OF 2016 CONCERNING MARK AND GEOGRAPHICAL INDICATIONS - Bakti Trisnawati (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2018)
Right on marks are a source of material wealth for their owners because they have economic value that can bring high profits. Marks in trade also have dualfunctions as competition tools and monopoly tools. Therefore, every mark owner needs to register his mark in order to get legal protection. Because in reality everyday there are many violations of the mark even though the mark has been registered, so the registered mark owner feels aggrieved. Violations due to people wanting to make a profit by cutting short the example of a registered and well-known mark, in addition to the Human Resources of the Directorate General of Intellectual Property itself also lacks control over the law on mark, so marks that should be rejected by many are approved. In addition, the Law Enforcement has indeed been implemented, but not maximal. This can be seen from the demands and fines of the Public Prosecutor and the Decision of the Panel of Judges is still very light